2015
DOI: 10.1007/s00261-015-0592-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative 13-year meta-analysis of the sensitivity and positive predictive value of ultrasound, CT, and MRI for detecting hepatocellular carcinoma

Abstract: MRI utilizing the hepatobiliary agent gadoxetate has the highest overall sensitivity and PPV, and may be the single optimal method for diagnosis of HCC. Non-contrast-enhanced US has the lowest sensitivity and PPV. More rigorous reference standards are needed to compare the performance of contrast-enhanced US with CT and MRI. Differences in sensitivity and PPV between CT and conventional gadolinium-enhanced MRI are not statistically significant overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
145
3
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(162 citation statements)
references
References 24 publications
4
145
3
10
Order By: Relevance
“…Although ultrasonography (US) is the most widely used modality for HCC screening and surveillance, the reported sensitivity of surveillance US is in the range of 40–81% with specificity of 80–100% [221225]. According to a recent meta-analysis study, among B-mode US, contrast-enhanced US (CEUS), contrast-enhanced (CT), and gadolinium-enhanced (MRI), B-mode US has the lowest sensitivity and positive predictive value (59.3, 77.4%) while the other three imaging modalities show similar pooled per-lesion sensitivity and positive predictive value (73.6–84.4%, 83.6–89.3%) [226]. Therefore, US is not advocated as a diagnostic test for confirmation due to overlapped imaging features of benign and malignant cirrhotic nodules on US.…”
Section: Diagnosis and Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…Although ultrasonography (US) is the most widely used modality for HCC screening and surveillance, the reported sensitivity of surveillance US is in the range of 40–81% with specificity of 80–100% [221225]. According to a recent meta-analysis study, among B-mode US, contrast-enhanced US (CEUS), contrast-enhanced (CT), and gadolinium-enhanced (MRI), B-mode US has the lowest sensitivity and positive predictive value (59.3, 77.4%) while the other three imaging modalities show similar pooled per-lesion sensitivity and positive predictive value (73.6–84.4%, 83.6–89.3%) [226]. Therefore, US is not advocated as a diagnostic test for confirmation due to overlapped imaging features of benign and malignant cirrhotic nodules on US.…”
Section: Diagnosis and Surveillancementioning
confidence: 99%
“…The AASLD removed CEUS from their guidelines in part because of the perceived possibility of false-positive HCC diagnosis in patients with intrahepatic cholangiocarcinoma [63, 242], but according to recent studies, wash-out time >55 s identified patients with HCC with the highest level of accuracy (92.7%) while wash-out time ≤55 s correctly identified the vast majority of non-HCC malignancies (diagnostic accuracy 98.3%) [244, 245]. In terms of diagnostic accuracy of CEUS for small HCC, recent meta-analysis studies demonstrated that pooled per-lesion sensitivity and positive predictive value of CEUS are similarly high (84.4 and 89.3%) compared with CT (73.6 and 85.8%) and MRI (77.5 and 83.6%), with better cost-effectiveness than CT or MRI [226, 246, 247]. A comparison of the diagnostic ability for hepatic nodules between CEUS using Sonazoid and contrast-enhanced CT showed that the sensitivity and accuracy were significantly higher for the former (95.4 and 94.7%) than the latter (85.2 and 82.3%) [248].…”
Section: Diagnosis and Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…The PPV was 89.3% for CEUS, 85.8% for CT and 94.2% for MRI [52]. In the STIC study, CEUS for HCC diagnosis had 69.8% sensitivity and 94.7% specificity [22].…”
Section: Livermentioning
confidence: 88%
“…The positive and negative predictive values are consistent with data reported in the literature when, as in our study, the gold standard consists of radiological investigations such as CT and MR. The reliability of ultrasound is lower when the gold standard is the histological study of explanted livers [30]. Moreover, not all patients with liver cirrhosis have an equal risk of developing HCC; therefore an increasing number of studies are being targeted to select “at risk” subpopulations to better focus the surveillance programs and reduce costs [10].…”
Section: Discussionmentioning
confidence: 99%